Psychosis in Patients with a History of Alcohol Use Disorder - Kusumadewi, Andrian Fajar; Hermanuaji Sihageng; Jennifer Andida; Muhammad Dicky Hertanto; Muhammad Jordan Diandraputra; Mulia Kharis; Raihan Hananto; Setiani Silvi Nurhidayah (Faculty of Medicine, Universitas Airlangga, 2023)
Introductions: Alcohol effects are not limited to one's physical state but also mental processes, including psychosis such as hallucinations or paranoia. Psychotic manifestations can also occur in general medical conditions or other neurological disorders associated with alcohol dependence. Cases: A 29-year-old man presented with a major depressive episode with psychotic symptoms. Since junior high school, the patient admitted to having a history of consuming crystal methamphetamine, heroin, and alcoholic drinks and often saw and heard the voices of 2 men. The patient was treated with Chlorpromazine for anxiety and Olanzapine for maintenance. The patient was allowed to go home with Olanzapine and scheduled for follow-up one week later. Discussions: Previous history indicates a possibility of alcohol-induced psychosis. However, specific diagnosis and management for such a condition is not possible due to no alcohol blood level tests available. Conclusions: The risk of psychotic disorders exists in all alcohol users, especially those with a history of psychosis and use of other addictive substances. A detailed history and appropriate investigations are helpful in monitoring the etiology and course of patients with alcohol-related psychosis.